(untitled) (MASKAY, 2013)
The research topic is focused on the Teleoperation of the Irobot Create mobile platform, which iRobot Corporation distributes. Teleoperation consists of sending commands to said platform to execute movements, using a PC-based HMI, and the teleoperation interface is also capable of showing images of the environment of the mobile platform with the help of a mounted analog camera.